Application of intense pulsed light – plasma – ultraviolet combined system on granular and powdered foods for microbial inactivation. (15th January 2023) - Hwang, Hee-Jeong; Lee, Ji-Yoon; Min, Sea C.; Chung, Myong-Soo
Abstract: The bactericidal effects of a self-designed device that combines intense pulsed light (IPL), plasma, and ultraviolet irradiation (UV) on granular and powdered foods, and the changes induced in the properties of the samples were studied. Samples were treated by combined IPL-plasma-UV system continuously. A maximum 1.33 ± 0.24-log reduction of microorganisms on sesame seeds were achieved using the combined system, while maximum 1.12 ± 0.18- and 0.59 ± 0.06-reductions were achieved using IPL-only and plasma-only systems, respectively. Using the combined system achieved maximum 0.41 ± 0.04- and 0.51 ± 0.05-log reductions of microorganisms on black pepper powder and red pepper powder, respectively, which have more holes, cracks, and crevices than sesame seeds. Significant changes in water activity, moisture content, and color were found in all samples due to drying caused by fast circulation or plasma treatment. So further research is needed to reduce the changes of the sample properties after the combined system. Highlights: IPL-plasma-UV combined device to decontaminate powdered foods has been constructed. Higher biocidal effects than the IPL-only and plasma-only systems were shown. Maximum 1.33 log reduction of microbial inactivation was achieved in sesame seeds. Sample with smooth surfaces and a few clogged holes had greater inactivation.